PENGEMBANGAN BAHAN AJAR SISTEM PERSAMAAN LINIER BERWAWASAN PENDIDIKAN MATEMATIKA REALISTIK BERORIENTASI BLENDED LEARNING - I Wayan Sumandya (FPMIPA IKIP PGRI Bali, 2016)
Learning Material Development Linear Equation System One and Two Variables instrument based on Realistic Mathematics Education oriented to Blended Learning. This study is aimed to material education the Linear Equation System One and Two Variables instrument based on Realistic Mathematics Education oriented to Blended Learning is order to improve student, activity dan student achievement. This present study is was development. In this study, the Linear Equation System One and Two Variables learning a Student Book, Teacher Guidebook and Lesson Plan are developed. This research was conducted at SMK N 1 Denpasar. The method used are observation, questionnaire, and test methods. In this study the validation sheet, observation sheets as enforceability of study, questionnaire as responses of students and teachers, observation sheet for students’ learning activity, and achievement test are alers mind. The data have been collected by descriptive processed. In this study, the instrument for learning Linear Equation System One and Two Variables that are validity, practically, and effectively.